2015
DOI: 10.1242/dev.117234
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-induced degradation dynamics set the pace for lateral root development

Abstract: Auxin elicits diverse cell behaviors through a simple nuclear signaling pathway initiated by degradation of Aux/IAA co-repressors. Our previous work revealed that members of the large Arabidopsis Aux/IAA family exhibit a range of degradation rates in synthetic contexts. However, it remained an unresolved issue whether differences in Aux/IAA turnover rates played a significant role in plant responses to auxin. Here, we use the well-established model of lateral root development to directly test the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…These results confirm the regulatory role that Aux/IAA rate motifs play in auxin responses. Moreover, the observed aberration in phyllotactic pattern caused by a slowed turnover of IAA28, likely reflecting an altered rate of primordia production at the shoot apex, supports the recently proposed model that Aux/IAAs are auxininitiated timers that synchronize developmental processes (Guseman et al, 2015).…”
Section: Degradation Rate Is Critical For Aux/iaa Function In Plantssupporting
confidence: 82%
See 1 more Smart Citation
“…These results confirm the regulatory role that Aux/IAA rate motifs play in auxin responses. Moreover, the observed aberration in phyllotactic pattern caused by a slowed turnover of IAA28, likely reflecting an altered rate of primordia production at the shoot apex, supports the recently proposed model that Aux/IAAs are auxininitiated timers that synchronize developmental processes (Guseman et al, 2015).…”
Section: Degradation Rate Is Critical For Aux/iaa Function In Plantssupporting
confidence: 82%
“…To test this, we generated transgenic Arabidopsis lines expressing heat shock-inducible fusions of IAA28 fragments with the bright YFP variant VENUS (Guseman et al, 2015). Following heat shock, seedlings were treated with auxin, and turnover of VENUS-IAA28 fragments was measured in root tips (Fig.…”
Section: Rate Motifs Tune Aux/iaa Degradation Rate In Plant Rootsmentioning
confidence: 99%
“…In previous work, we demonstrated the importance of auxin-induced IAA degradation rate in tuning cellular sensitivity to auxin (19,28,29). In circuits containing only an IAA and AFB receptor, IAA-IAA PB1 interactions had modest or no influence on IAA degradation rates (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…We chose to test slr because of the striking solitary root phenotype for which it was named (26). We and others have previously demonstrated that pIAA14::slr transgenic plants largely recapitulate the phenotype of the slr mutant where the initiation of nearly all lateral roots is inhibited (27,28). We reasoned that a loss of repression Table S1 for specific residues that were mutated in each domain.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, close to 900 F-box-type E3 ligases are annotated in the Arabidopsis genome, which is 10-fold more than in the human genome . The role of protein ubiquitination by E3 ligases in plants is illustrated by numerous studies, mostly at the single protein level, revealing that this PTM acts in the plant's response to drought stress, temperature tolerance, and coordination of responses to phytohormones, such as auxin, brassinosteroids, and jasmonates (Cui et al, 2012;Cuéllar Pérez and Goossens, 2013;Guseman et al, 2015). E3 ligases have been shown to be essential regulators of plant immunity, and many microbes even seem to have evolved a way to sabotage the host UPS (Marino et al, 2012).…”
Section: The Importance Of Ubiquitination In Plantsmentioning
confidence: 99%